Allergen Recognition by Innate Immune Cells: Critical Role of Dendritic and Epithelial Cells - Salazar, Fabian; Ghaemmaghami, Amir (Frontiers in Immunology, 2013)
Allergy is an exacerbated response of the immune system against non-self-proteins called allergens and is typically characterized by biased type-2 T helper cell and deleterious IgE mediated immune responses. The allergic cascade starts with the recognition of allergens by antigen presenting cells, mainly dendritic cells, culminating in mast cell sensitization and triggering. Dendritic cells have been demonstrated to play a crucial role in orchestrating allergic diseases. Using different C-type lectin receptors dendritic cells are able to recognize and internalize a number of allergens from diverse sources leading to sensitization. Furthermore, there is increasing evidence highlighting the role of epithelial cells in triggering and modulating immune responses to allergens. As well as providing a physical barrier, epithelial cells can interact with allergens and influence dendritic cells behaviour through the release of a number of Th2 promoting cytokines. In this review we will summarise current understanding of how allergens are recognised by dendritic cells and epithelial cells and what are the consequences of such interaction in the context of allergic sensitisation and downstream events leading to allergic inflammation. Better understanding of the molecular mechanisms of allergen recognition and associated signalling pathways could enable developing more effective therapeutic strategies that target the initial steps of allergic sensitisation hence hindering development or progression of allergic diseases.